2008
DOI: 10.1097/ftd.0b013e31817fd4d4
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Lamotrigine with Data from Therapeutic Drug Monitoring in German and Spanish Patients with Epilepsy

Abstract: This study develops a population pharmacokinetic model for lamotrigine (LTG) in Spanish and German patients diagnosed with epilepsy. LTG steady-state plasma concentration data from therapeutic drug monitoring were collected retrospectively from 600 patients, with a total of 1699 plasma drug concentrations. The data were analyzed according to a one-compartment model using the nonlinear mixed effect modelling program. The influences of origin (Germany or Spain), sex, age, total body weight, and comedication with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 47 publications
8
28
0
2
Order By: Relevance
“…This unexplained variability was of similar magnitude to those reported in earlier studies [7,[13][14][15][16][32][33][34] .…”
Section: Discussionsupporting
confidence: 76%
“…This unexplained variability was of similar magnitude to those reported in earlier studies [7,[13][14][15][16][32][33][34] .…”
Section: Discussionsupporting
confidence: 76%
“…Our findings allowed us to estimate the LTG concentration in Japanese patients with epilepsy by applying coefficients for age, gender, LTG dose, and the AED regimens to a multiple regression model. In addition, the r 2 value for the relation between the measured and estimated LTG concentrations was 0.72 (p<0.001) in our model, which was equal that reported for a multiple regression model 10) (r 2 =0.72) and better than that for a population pharmacokinetic model 14) (r 2 =0.62) in Caucasian patients (Fig. 5).…”
Section: )supporting
confidence: 59%
“…On the other hand, the effects of phenobarbital on CL LTG was not shown (this covariate was not well represented in our population). Earlier studies have reported about significant influence of phenobarbital on mean population value of lamotrigine clearance [43,45].…”
Section: Lamotriginementioning
confidence: 99%
“…Equation for the final model which described value of population LTG clearance was as following [10]: Previous studies have shown that total body weight described part of the interindividual variability of LTG clearance in other studies, too [41][42][43][44][45][46]. Increase of CL LTG with increase in TBW was noted in a heterogenous Spanish population and also in pediatric and elderly population of epileptic patients [41,42,44,46].…”
Section: Lamotriginementioning
confidence: 99%
See 1 more Smart Citation